An experiment on the impact of coaches' and athlete leaders' competence support on athletes' motivation and performance. (11th September 2018) - Mertens, Niels; Boen, Filip; Vande Broek, Gert; Vansteenkiste, Maarten; Fransen, Katrien
Abstract : Purpose: Grounded in the Cognitive Evaluation Theory, the present experiment aimed to compare the relative impact of competence support provided by coaches versus athlete leaders on players' competence satisfaction, intrinsic motivation, and performance. Methods: We recruited 18 existing competitive male basketball teams (ie, 126 players) to participate in the experiment. Each team was randomly assigned to one of three conditions: (a) the coach provided competence support (ie, by encouraging, providing positive feedback, and expressing team confidence); (b) the athlete leader provided competence support; or (c) neither the coach, nor the athlete leader provided competence support (ie, control condition). Results: Teams in which the athlete leader provided competence support reported higher levels of competence satisfaction and intrinsic motivation than teams in the control condition, a difference that did not emerge when the coach provided competence support. Furthermore, teams in which either the coach or the athlete leader supported team members' competence performed better compared to teams in the control group. Conclusion: Our findings highlight the importance of providing competence support to enhance team performance. Given athlete leaders' unique impact on teammates' competence satisfaction and motivation, instructing athlete leaders how to provide competence support constitutes an important motivational pathway for coaches to optimize team functioning.